Copper-zirconia, zirconia-based metallic glass - Shi, Darren Dingji. (2012)
Bulk glass-forming alloys have emerged over the past fifteen years with attractive properties and technological promise. One of the attractions in amorphous alloys is their unique set of mechanical properties. It is discovered that at room temperature, these amorphous alloys exhibits relatively high strengths compared to their polycrystals counterparts. Such superior attributes has led to promising applications in a wide area of industries.